An ecological study of Indian open drain sewage and it’s treatment - Singh, Ajay; Patidar, SK; Sangwan, Vikramaditya (Ecological Questions, 2023)
The disposal of a large volume of untreated and partially treated domestic wastewater is causing pollution of various water sources. Sewage treatment involving conventional wastewater treatment technologies is costly. In the present study, in-situ treatment of sewage using a commercially effective microbial consortium was investigated in two community open drains of Chanarthal village in Haryana state of India. The pH, turbidity, BOD, and COD were determined in accordance with standard methods. The optimum dose for treatment in the batch study was 1ml/L, and the optimum time for treatment was 5 days. The batch study results were used for continuous in-situ treatment study performed in drains over a period of six weeks. The turbidity, BOD, and COD removal were 60.1, 82.1, and 64.7% in the batch study and 40.1, 61.1, and 56.4% in the continuous in-situ treatment study. It was also observed that a higher dose of microbial consortia gives the same performance as low doses at a later stage of the study.